Understorey vegetation in young naturally regenerated and planted birch (Betula spp.) stands on abandoned agricultural land - Tea Tullus; Arvo Tullus; Elle Roosaluste; Ants Kaasik; Reimo Lutter; Hardi Tullus (New Forests, 2013)

Past and Present Effectiveness of Protected Areas for Conservation of Naturally and Anthropogenically Rare Plant Species - AIN VELLAK; EVA‐LIIS TUVI; ÜLLE REIER; REIN KALAMEES; ELLE ROOSALUSTE; MARTIN ZOBEL; MEELIS PÄRTEL (Conservation Biology, 2009)
The Global Strategy of Plant Conservation states that at least 60% of threatened plant species should be within protected areas. This goal has been met in some regions with long traditions of plant protection. We used gap analysis to explore how particular groups of species of conservation interest, representing different types of natural or anthropogenic rarity, have been covered by protected areas on a national scale in Estonia during the last 100 years. Species‐accumulation curves indicated that plant species that are naturally rare (restricted global or local distribution, always small populations, or very rare habitat requirements) needed almost twice as many protected areas to reach the 60% target as plant species that are rare owing to lack of suitable management (species depending on grassland management, moderate forest disturbances, extensive traditional agriculture, or species potentially threatened by collecting). Temporal analysis of the establishment of protected areas suggested that grouping plant species according to the predominant cause of rarity accurately reflected the history of conservation decision making. Species found in very rare habitats have previously received special conservation attention; species dependent on traditional extensive agriculture have been largely ignored until recently. Legislative initiative and new nature‐protection schemes (e.g., Natura 2000, network of protected areas in the European Union) have had a positive influence on all species groups. Consequently, the species groups needing similar action for their conservation are sensitive indicators of the effectiveness of protected‐area networks. Different species groups, however, may not be uniformly conserved within protected areas, and all species groups should fulfill the target of 60% coverage within protected areas.

Monitoring of Biological Diversity: a Common‐Ground Approach - TIIT TEDER; MARI MOORA; ELLE ROOSALUSTE; KRISTJAN ZOBEL; MEELIS PÄRTEL; URMAS KÕLJALG; MARTIN ZOBEL (Conservation Biology, 2007)
Practical approaches to monitoring biological diversity vary widely among countries, and the accumulating data are frequently not generalizable at the international scale. Although many present monitoring schemes, especially in developed countries, produce highly complex data, there is often a lack of basic data about the level and spatial distribution of biodiversity. We augmented the general framework for improving biomonitoring, proposed by , and identified its core tasks and attributes. The first priority for a more unified biodiversity monitoring is to agree on a minimum set of core tasks and attributes, which will make it possible to build a standardized biomonitoring system even in countries with few resources. Our scheme has two main organizational levels—taxa and ecosystems. The basic elements of the biomonitoring system proposed are recording of presence and absence of taxa and ecosystems in a target area, mapping of their distribution in space, and assessment of their status. All the elements have to be repeated over time. Although these tasks are fundamental, they are frequently not considered in currently functioning biomonitoring programs. The whole system has to be hierarchical and additive: if more resources are available, new activities may be added to the basic routine. Agreeing on a common standard will facilitate aggregating measures of biodiversity status and trends into regional and global indices. This information will relate directly to several Convention on Biological Diversity indicators for assessing progress toward the 2010 Biodiversity Target.